The Effect of Elderly Gymnastics on the Level of Independence of Daily Activities in the Community - Nur Insani; Esa Zahirah; Susanti Delina (CV. Get Press Indonesia, 2025)
Aging is a natural process characterized by a decrease in physical, psychological and social functions, which often affects the independence of the elderly in carrying out daily activities. One of the efforts to maintain the independence of the elderly is through regular and appropriate physical activities, such as elderly Gymnastics. Purpose: this study aims to determine the effect of elderly Gymnastics on the level of independence in daily activities in the elderly in the community. Methods: this study uses quantitative design with quasi-experiment pretest-posttest approach. Samples of 30 elderly were taken by purposive sampling from an elderly community in the working area of Ambacang Padang Health Center. Intervention in the form of elderly Gymnastics is carried out for 4 weeks with a frequency of 3 times a week. Data were collected using the ADL (Activities of Daily Living) instrument and analyzed using the Wilcoxon test. Results: the results showed a significant increase in the elderly independence score after participating in gymnastics (p = 0.001). Before the intervention, most of the elderly were at a mild to moderate level of dependence, while after the intervention, the majority showed complete independence in carrying out daily activities such as bathing, dressing, eating, to walking. Implications: elderly Gymnastics is an effective, easy-to-perform, and routinely feasible intervention in public health programs to support the quality of life and independence of the elderly. Conclusion: elderly Gymnastics has a significant positive effect on increasing the independence of the daily activities of the elderly in the community.